Complete Genome Sequence of the Plant Growth-Promoting Bacterium Hartmannibacter diazotrophicus Strain E19T. (9th September 2019) - Suarez, Christian; Ratering, Stefan; Hain, Torsten; Fritzenwanker, Moritz; Goesmann, Alexander; Blom, Jochen; Chakraborty, Trinad; Bunk, Boyke; Spröer, Cathrin; Overmann, Jörg; Schnell, Sylvia
Abstract : Strain E19 T described as Hartmannibacter diazotrophicus gen. nov. sp. nov. was isolated from the rhizosphere of Plantago winteri from a natural salt meadow in a nature protection area. Strain E19 T is a plant growth-promoting rhizobacterium able to colonize the rhizosphere of barley and to promote its growth only under salt stress conditions. To gain insights into the genetic bases of plant growth promotion and its lifestyle at the rhizosphere under salty conditions, we determined the complete genome sequence using two complementary sequencing platforms (Ilumina MiSeq and PacBio RSII ). The E19 T genome comprises one circular chromosome and one plasmid containing several genes involved in salt adaptation and genes related to plant growth-promoting traits under salt stress. Based on previous experiments, ACC deaminase activity was identified as a main mechanism of E19 T to promote plant growth under salt stress. Interestingly, no genes classically reported to encode for ACC deaminase activity are present. In general, the E19 T genome provides information to confirm, discover, and better understand many of its previously evaluated traits involved in plant growth promotion under salt stress. Furthermore, the complete E19 T genome sequence helps to define its previously reported unclear 16S rRNA gene-based phylogenetic affiliation. Hartmannibacter forms a distinct subcluster with genera Methylobrevis, Pleomorphomonas, Oharaeibacter, and Mongoliimonas subclustered with genera belonging to Rhizobiales .